2016
DOI: 10.1002/2015jd024460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geomagnetic activity on the northern annular mode: QBO dependence and the Holton-Tan relationship

Abstract: Mutually conflicting results have been presented in earlier studies on the long‐term relation of geomagnetic activity (GA) and the winter northern annular mode (NAM) and its modulation by quasi‐biennial oscillation (QBO). Some studies have found a stronger positive relation in the easterly phase of the QBO, while in other studies a stronger positive relation was found in the westerly phase of the QBO. Using QBO reconstruction from the beginning of the twentieth century we find that the QBO modulation of the GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 61 publications
(114 reference statements)
7
30
0
Order By: Relevance
“…In fact SSW occurrence rate is highest in winters with low Ap (low EEP) and QBO-E, when SSW occurs in 15 out of 17 winters. This result agrees with earlier studies (Maliniemi et al, 2013(Maliniemi et al, , 2014(Maliniemi et al, , 2016(Maliniemi et al, , 2018Salminen et al, 2019) showing that the effect of energetic electron precipitation on polar vortex is stronger in QBO-E winter months. In QBO-E winters low EEP weakens the polar vortex and SSWs occur more often, while high EEP strengthens the polar vortex and SSWs occur less.…”
Section: Discussionsupporting
confidence: 93%
“…In fact SSW occurrence rate is highest in winters with low Ap (low EEP) and QBO-E, when SSW occurs in 15 out of 17 winters. This result agrees with earlier studies (Maliniemi et al, 2013(Maliniemi et al, , 2014(Maliniemi et al, , 2016(Maliniemi et al, , 2018Salminen et al, 2019) showing that the effect of energetic electron precipitation on polar vortex is stronger in QBO-E winter months. In QBO-E winters low EEP weakens the polar vortex and SSWs occur more often, while high EEP strengthens the polar vortex and SSWs occur less.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with the studies by Palamara and Bryant () and Maliniemi et al (, ), which concluded that the EEP effect on the NAO/NAM is larger in the QBO‐E phase. Lu et al () found that the EEP effect in May is stronger if the deseasonalized QBO at 50 hPa is westerly.…”
Section: Eep Effect Separately In the Two Qbo Phasessupporting
confidence: 93%
“…The dynamical effects on the southern polar vortex are much weaker, less significant, and even opposite to those in the Northern Hemisphere (Arsenovic et al, ; Lu et al, ; Tomikawa, ). The variations of polar vortex are also seen in the Northern Annular Mode (NAM) and North Atlantic Oscillation (NAO) surface climate modes (Baldwin & Dunkerton, ), and EEP (or geomagnetic activity as EEP proxy) has been found to correlate with these modes in several studies (Baumgaertner et al, ; Maliniemi et al, , ; Palamara & Bryant, ).…”
Section: Introductionmentioning
confidence: 98%
“…A positive U anomaly emerges in the subtropical mid‐stratosphere in December and progresses poleward and downward (via wave–mean flow interaction), reaching the troposphere in February. These results are in agreement with earlier studies of GA and SA effects on winter surface climate (Ineson et al ., ; Gray et al ., ; Maliniemi et al ., ) and support the two different top‐down mechanisms related to particle precipitation and solar UV.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies of long‐term surface climate in winter have shown that the positive NAO response related to sunspot activity (SA) is obtained in late winter (February) (Gray et al ., ), whereas in early winter (December) a positive SLP anomaly over the Azores is observed 2–4 years after the sunspot maximum (Gray et al ., ; ). Solar wind driven particles/geomagnetic activity (GA) has a strong positive relation with NAO without any lag (Maliniemi et al ., ). GA maximizes a few years after sunspot maximum due to the occurrence of high‐speed solar wind streams from coronal holes (Ruzmaikin and Feynman, ; Mursula et al ., ).…”
Section: Introductionmentioning
confidence: 99%